Pengaruh Kemampuan Digitalisasi Dan Jiwa Entrepreneur Terhadap Keberhasilan Usaha Kecil Dan Mikro (Ukm): Analisis Peran Dukungan Pemerintah Sebagai Variabel Moderasi - Tesa Rahayu Milianda (Brida Provinsi Jambi, 2025)
This study aims to analyze the influence of digitalization capability, entrepreneurial spirit, andgovernment support on the success of small and micro enterprises in Jambi City, focusing onthe Sahabat Sehati UKM community. The main issues faced by MSEs in this communityinclude low digital literacy, a lack of strong entrepreneurial spirit, and suboptimal governmentsupport in sustaining business development. This research uses a quantitative approach withdata collected through questionnaires distributed to 150 MSEs actors in the culinary, fashion,and service sectors. Data were analyzed using Structural Equation Modeling based on PartialLeast Square with the Smart PLS 3.0 application. The results show that digitalization capabilityhas a negative and insignificant effect on MSEs success, while entrepreneurial spirit andgovernment support have a positive and significant effect. Moreover, government supportstrengthens the relationship between digitalization capability and MSEs success but does notstrengthen the relationship between entrepreneurial spirit and UKM success. These findingshighlight the importance of more structured digital empowerment programs and moresustainable government support in MSEs development. Keywords: Digitalization capability, entrepreneurial spirit, government support, MSEssuccess